A humanização da "coisa" em Os escravos, de Castro Alves - Campos, Éverton Luís Matos de (2014)
This master thesis starts from the study of Castro Alves poetical text (Os Escravos), in order to understand how "The Poet of the Slaves" pursuits to humanise the captive (livestock/animal/property) before the eyes of the white readers of his era, as well as his motivation. We start from the understanding that the literary work is an organism and not a mere junction of lyrical texts with a profusion of themes. We propose a thematic and methodological division within the work, thus mapping the crucial steps to the humanisation of the black slave. In this point, the conceptions of Gorender (1985) and Mattoso (2003) presented us bases to understand the Brazilian enslaver nineteenth century mindset. This division provided us also understand how the Bahian poet merges, in the same figure, the black and the Brazilian people, in counterpoint to the enslaver that represents the monarchy, giving the lyric a republican sense. Our analysis also focus on the enunciative and dialogical form of this lyrical compositions, from the studies of Bakhtin (1992) about these themes